STUDYING THE NOISE LEVELS AT AN ELECTRICAL POWER STATION - Abdulwahhab Abdulrazzak, Ibtihaj; Abdulwahhab Abdulrazzaq, Ali (Journal of Engineering and Sustainable Development, 2018)
Studying the noise levels has great significance by those whose concerned with the environment and human, because of its negative impact on human health and his performance. This paper presents a measuring of noise in the positions of the power station south of Baghdad includes 15 positions inside the station’s building and 15 positions outside the station’s building. The noise level measured in decibels by using the noise level meter (NLM). The results showed that the values of the noise level at positions outside the station’s building are between (66.9dB – 88.1dB), which are for the positions of (p3-p15) are out of allowable levels according to the allowable limits for the WHO (67 dB), while the positions (p1 & p2) are within the allowable limits. The noise levels at positions inside the station’s building (p1-p15) are (66.1dB –86.2dB) all the values are out of the allowable level for WHO (57 dB). To reduce the negative effects of noise, special materials should be used on the walls of the building to absorb the noise, as well as to minimize the exposing time to the noise in order to protect the workers’ health.